IKK-Dependent, NF-κB-Independent Control of Autophagic Gene Expression - Comb, William C. (2010)
The induction of mammalian autophagy, a cellular catabolic bulk-degradation process conserved from humans to yeast, was recently shown to require IKK, the upstream regulator of the NF-κB pathway. Interestingly, it was shown that this response did not involve classic NF-κB. Thus, the mechanism by which IKK promotes stimulus-induced autophagy is largely unknown. Here we investigate the role of IKK/NF-κB in response to nutrient deprivation, the classic autophagy-inducing stimulus. IKK and both the classic and non-canonical pathways of NF-κB are robustly induced in response to cellular starvation. Notably, cells lacking either catalytic subunit of IKK (IKKα or IKKβ) fail to induce autophagy in response to cellular starvation. Importantly, we show that IKK activity but not NF-κB, controls basal expression of the pro-autophagic gene LC3. We further demonstrate that starvation induces the expression of LC3 and two other essential autophagic genes, ATG5 and Beclin-1, in an IKK-dependent manner. These results demonstrate that the IKK complex is a central mediator of starvation-induced autophagy in mammalian cells and suggest that this requirement occurs at least in part through the regulation of autophagic gene expression. Interestingly, NF-κB subunits are dispensable for both basal and starvation-induced expression of pro-autophagic genes. However, starvation-induced activation of NF-κB is not inconsequential as increases in expression of anti-apoptotic NF-κB target genes such as cIAP2 is observed in response to cellular starvation. Thus, IKK likely plays multiple roles in response to starvation by regulating NF-κB-dependent anti-apoptotic gene expression as well as controlling expression of autophagic genes through a yet undetermined mechanism.